2009
DOI: 10.1111/j.1471-0528.2009.02174.x
|View full text |Cite
|
Sign up to set email alerts
|

Is informed choice in prenatal testing universally valued? A population‐based survey in Europe and Asia

Abstract: Objective  Informed choice has become an integral part of healthcare provision. We investigated the extent to which informed choice in the context of prenatal testing is universally valued. Design  The value attached to parental choice in prenatal testing and the perceived importance of significant others’ views when making test decisions were assessed in a cross‐sectional, descriptive study. Sample and setting  Male and female participants from general population samples in six countries: the UK (n = 210), th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 15 publications
0
20
0
1
Order By: Relevance
“…Previous research has shown variation in women's views on prenatal testing between countries with respondents from Northern European countries more likely to value parental choice in prenatal testing than their counterparts in Southern Europe and Asia. 31 Variation in women's preferences between countries raises the question of whether differences exist between cultural groups within countries. There is some evidence suggesting ethnic minority groups in Western countries differ in how they view and use prenatal screening and testing.…”
Section: Direct Choice Between Nipt Invasive Testing or No Testmentioning
confidence: 99%
“…Previous research has shown variation in women's views on prenatal testing between countries with respondents from Northern European countries more likely to value parental choice in prenatal testing than their counterparts in Southern Europe and Asia. 31 Variation in women's preferences between countries raises the question of whether differences exist between cultural groups within countries. There is some evidence suggesting ethnic minority groups in Western countries differ in how they view and use prenatal screening and testing.…”
Section: Direct Choice Between Nipt Invasive Testing or No Testmentioning
confidence: 99%
“…An alternative viewpoint is that women who act in line with the values of significant others, such as GPs, can exercise an informed choice if the individual 'chooses' to act in line with the attitudes of significant others. 128 General practitioners had positive attitudes towards antenatal SCT screening, as they believed in the benefits of early diagnosis in facilitating timely choice for pregnant women, having seen the effect that sickle cell disease had on their patients. They expressed the importance of educating patients about these conditions, particularly those at risk.…”
Section: Discussionmentioning
confidence: 99%
“…Deux nouvelles études semblent montrer que certaines familles ne sont pas particulièrement demandeuses de pouvoir décisionnaire, du moins tel qu'il leur est proposé actuellement. Si ce concept se confirme, il devra être pris en compte [17].…”
Section: Information Et Cultureunclassified